PLATELET-RICH PLASMA IN ANTI-AGING AND AESTHETIC MEDICINE - Yuliya Fedorchenko (Anti-Aging Eastern Europe)
Skin aging is a multifactorial process influenced by intrinsic and extrinsic factors, leading to structural and functional deterioration, including wrinkles, laxity, pigmentation, and barrier dysfunction. Platelet-Rich Plasma (PRP) has emerged as a novel regenerative therapy in anti-aging and aesthetic medicine due to its ability to stimulate collagen production, tissue repair, and neo-angiogenesis through autologous growth factors. PRP has demonstrated significant efficacy in improving skin texture, tone, and elasticity, particularly when combined with microneedling, dermal fillers, or fractional lasers. In addition to facial rejuvenation, PRP shows promise in treating androgenetic alopecia (AGA), enhancing hair density and thickness, and reducing shedding with minimal adverse effects. The treatment’s safety profile, versatility, and shorter recovery periods make it an appealing alternative to conventional anti-aging therapies. Despite its clinical potential, further research is warranted to standardize protocols, elucidate cellular mechanisms, and optimize outcomes for widespread application in aesthetic dermatology.